Math, asked by legendgammerstudent, 6 months ago

simplify:2x²y-[4y²x-{3x²y-(4x²y-2xy² please explain step by step​

Answers

Answered by 567sweetysharma
0

Step-by-step explanation:

2x^2y-4y^2x-3x^2y-4x^2-2xy^2

= - 4x^2y-x^2y-6y^2x

= - 5x^2y-6y^2x

Answered by anthonypaulvilly
0

Answer:

      x²y - 2xy²

Step-by-step explanation:

  2x²y - [4y²x - { 3x²y -( 4x²y - 2xy² )} ]​

= 2x²y - [4y²x - { 3x²y - 4x²y + 2xy²} ]​

= 2x²y - [4y²x - 3x²y + 4x²y - 2xy² ]​

= 2x²y - 4y²x + 3x²y - 4x²y + 2xy²

= 2x²y + 3x²y - 4x²y - 4y²x + 2xy²

= x²y - 2xy²

Similar questions